Comparison of Some Statistical Criteria for Determining Factors Affecting Anemia - Nawras Majid Zaki, Dr. Ameena KareemEssa (Mathematical Statistician and Engineering Applications, 2022)
Anemia was a widespread disease, occurring in persons where there were not enough red cells to transport oxygen throughout the body. Anemia was diagnosed at the level of simple and severe i.e. temporary and permanent, the normal ratio in males was 13.5 g/dL, Then the use of exploratory factor analysis and two criteria for comparison, namely the criterion of the least partial average and the criterion of parallel analysis, it was found through this study that the criterion of the least partial average had four factors, while the standard of parallel analysis had three influential factors, and the proportion of the explained variance of the criterion of the least partial average was higher than The percentage of the explained variance of the parallel analysis criterion.